Is a high initial World Federation of Neurosurgery (WFNS) grade really associated with a poor clinical outcome in elderly patients with ruptured intracranial aneurysms treated with coiling?. (24th May 2013) - Iosif, Christina; Di Maria, Federico; Sourour, Nader; Degos, Vincent; Bonneville, Fabrice; Biondi, Alessandra; Jean, Betty; Colonne, Chantal; Nouet, Aurelien; Chiras, Jacques; Clarençon, Frédéric
Abstract : Background: Coiling of ruptured intracranial aneurysms in elderly patients remains debatable in terms of technical feasibility and clinical outcome. Aims: In this observational cohort study we aimed to assess the technical feasibility, complication profile and clinical outcomes of elderly patients with subarachnoid hemorrhage (SAH) treated with endovascular therapy. Methods: The study included 59 consecutive patients (47 women) aged ≥70 years (mean age 76 years, range 71–84) admitted to our institution with SAH from January 2002 to July 2011. The patients were treated for 66 aneurysms (regular coiling: n=62 (94%), balloon-assisted technique: n=2 (3%), stent and coil technique: n=2 (3%)). World Federation of Neurosurgery (WFNS) grade at admission was 1 in 13 patients, 2 in 23 patients, 3 in 8 patients, 4 in 11 patients and 5 in 4 patients. We analysed data by univariate and multivariate statistical analyses with an emphasis on the initial clinical situation, complications and clinical outcome. Results: The technical success rate was 98% with a procedure-related deficit rate of 10% and procedure-related death rate of 5%. The Glasgow Outcome Scale score at 6 months was 1 in 15 patients (25.4%), 2 in 8 patients (13.6%), 3 in 14 patients (23.7%), 4 in 11 patients (18.6%) and 5 in 11 patients (18.6%). Patients admitted with a high initial WFNS grade did not differ statistically in terms of clinical outcome. The final clinical outcome was not significantly correlated with age, initial Fisher score or procedure-related complications. Conclusions: Endovascular treatment of elderly patients with ruptured cerebral aneurysms is feasible, safe and beneficial regardless of the presenting WFNS score.